Chemical oxygen demand (COD) degradation of herbal, tofu and fertilizer wastewater using UV/Ozone oxidation methods. (May 2019) - Hadiyanto,; Silviana,; PAdetya, N; Pratiwi, M E; Aripratama, A D
Abstract: The herbal, tofu and fertilizer industries contribute considerable waste. Unprocessed waste disposal can cause environmental pollution. The waste contains chemical oxygen demands (COD), and organic substances can be degraded by Advanced Oxidation Processes (AOPs) degradation method. The process of AOPs in this study used a combination of UV rays and ozone to produce hydroxyl radicals. This study was aimed to investigate the effect of UV, Ozone and UV-Ozone methods on COD degradation of herbal waste, tofu, and fertilizer. The result showed that the optimum degradation was obtained at experiment by using UV/ozone method. The COD degradation at tofu wastewater was from 1308 to 942 ppm, herbal wastewater was from 1011 to 414 ppm, and fertilizer wastewater was from 510 to 89 ppm by the use of 4 hours UV-Ozone method.